PENGARUH MEDIA PEMBELAJARAN PUZZLE TERHADAP KEMAMPUAN SISWA MEMAHAMI BENTUK BANGUN DATAR DI KELAS 2 SDN 20 TUNGKAL ILIR (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The learning process in elementary schools often faces challenges related to low student participation and understanding, particularly in mathematics, which is frequently perceived as a difficult subject. Preliminary observations in Grade II of SDN 20 Tungkal Ilir revealed that geometry lessons on plane figures were still teacher-centered and relied solely on textbooks, resulting in students’ lack of enthusiasm and passive engagement in learning activities. One potential solution is the use of puzzle media, as it has been proven to enhance concentration, critical thinking, creativity, and children’s fine motor coordination. This study aims to analyze the effect of puzzle media on students’ ability to understand the concept of plane figures in Grade II. The focus includes comparing students’ learning outcomes before and after the use of puzzle media, as well as examining its impact on motivation and engagement in the learning process. It is expected that the application of puzzle media will improve students’ conceptual understanding of plane figures, foster more active participation, and optimize the quality of mathematics learning in elementary schools.